1966
DOI: 10.1002/pssb.19660160112
|View full text |Cite
|
Sign up to set email alerts
|

Colour Centres in X‐Irradiated NaCl:Ag and NaCl:(Ag + Ca) Crystals

Abstract: A study is made of colour centres induced by X-irradiation a t room temperature in NaC1:Ag and NaCl: (Ag + Ca). It is shown that the induced bands in NaCl: Ag are strongly dependent on the concentration of Ag as well as on the irradiation time and also that the B-, C-, and D-bands have a complex structure. Three components of the B-band, four of the C-band and two of the D-band are found at liquid nitrogen temperature. Optical bleaching in the F-light shows that only a component of the B-, C-, and D-bands is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

1966
1966
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
1
1
Order By: Relevance
“…But though the calcium concentration is very low, some absorption a t 250 nm ( K x 1 cm-l) and 260 nm is still there. From our data we cannot conclude, as previously suggested [4], that the absorption bands a t 250 and 260 nm depend on the calcium content and do not appear in crystals containing no calcium.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…But though the calcium concentration is very low, some absorption a t 250 nm ( K x 1 cm-l) and 260 nm is still there. From our data we cannot conclude, as previously suggested [4], that the absorption bands a t 250 and 260 nm depend on the calcium content and do not appear in crystals containing no calcium.…”
Section: Discussioncontrasting
confidence: 82%
“…I n the ultraviolet between 200 and 230 nm a series of absorption bands show up which have been attributed to vibronically allowed transitions 4d10 --f 4dQ5s in the Ag+ ion [3]. Adjacent to these well-known Ag+ absorption bands we found in most of our Ag+-doped NaCl crystals absorption bands at 250, 260, and occasionally also at 231, 240 nm.l) Tope and Haragea [4] have seen these four bands when they measured NaCl crystals doped with silver and calcium at -180 "C. These authors speculated that the centre causing the four absorption bands might possibly be due to an Ag, Ca, and 0 combination.…”
Section: Introductionsupporting
confidence: 55%
“…Etzel and Schulman suggested that the B-band would be due to an electron trapped on a silver ion in the vicinity of a vacancy [2]. Furthermore, it was shown by Topa and Haragea [3] that the B-bands in X-rayed and electrolytically coloured NaC1:Ag crystals are not the same. This paper presents properties of the Bcentres in additively coloured silver-doped KC1 crystals.…”
Section: Introductionmentioning
confidence: 99%